EFEKTIVITAS MEDIA AUDIO VISUAL UNTUK MENINGKATKAN PEMAHAMAN SISWI KELAS XI SMA AN NUR BULULAWANG PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DALAM TATA CARA PENYELENGGARAAN JENAZAH - Lilik Nur Fadhilah; Chalimatus Sadiyah; Devi Wahyu Ertanti (VICRATINA, 2019)
The learning process using media audio visual less effective, especially in class XI regular because of the school just supply a video and it’s generally not in detailed. With the effectiveness of the media audio visual on the subject of education religion islam is expected to improve the understanding student in the way of bier. Research carried out in high school An Nur Bululawang Malang. The purpose of this study is the effectiveness of the media audio visual to improve the understanding student grade of high school XI An Nur Bululawang Malang   poor on the subject of education religion islam in the way of mortuary and increased understanding after the effectivenessof the media audio visual student with a variety of a version in class XI high school An Nur Bululawang on the subject of education religion islam in the way of bier.  Methods used is a method abservations, the test, an interview and documentation. Then data obtained analyzed with the way the reduction of data, the presentation of the data, and the withdrawal of the conclusion. Checking the data with triangulasi technique with observations partisipatif, in-depth interviews and documentation to the source of the data that the same in unison. In conclusion high school An Nur Bululawang apply the effectiveness of the media audio visual to improve the understanding sudent. Keywords: Efekitivitas, Media Audio Visual, Peningkatan Pemahaman Siswi.